2004
DOI: 10.1007/s00125-004-1455-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of N?-carboxymethyl-lysine, an advanced glycation end product, are associated with proliferative diabetic retinopathy and macular oedema

Abstract: Aims/hypothesis. Diabetic retinopathy is a frequent microvascular complication. In search of novel risk markers, we analysed the association between serum levels of the major advanced glycation end product N ε -carboxymethyl-lysine (CML) and prevalence of advanced stages of retinopathy in Type 2 diabetic patients without nephropathy. Methods. We carried out a case-control study of Type 2 diabetic patients with and without advanced stages of diabetic retinopathy. Retinopathy and macular oedema were defined acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 10 publications
(19 reference statements)
1
102
2
1
Order By: Relevance
“…Recent work has suggested that monitoring oxidative stress in parallel with hyperglycaemia may help to identify subsets of patients at high risk of advancement of diabetic retinopathy [19][20][21]. Carboxymethyl-lysine (CML), a product of glycooxidation and lipoxidation reactions, is often regarded as a general marker of oxidative stress [42] and a number of studies have shown cross-sectional associations between serum CML levels and the severity of diabetic retinopathy [43][44][45]. In most cases, however, serum CML levels strongly correlate with HbA 1c [46], suggesting that serum CML may not provide any additional risk information beyond that provided by monitoring mean levels of glycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has suggested that monitoring oxidative stress in parallel with hyperglycaemia may help to identify subsets of patients at high risk of advancement of diabetic retinopathy [19][20][21]. Carboxymethyl-lysine (CML), a product of glycooxidation and lipoxidation reactions, is often regarded as a general marker of oxidative stress [42] and a number of studies have shown cross-sectional associations between serum CML levels and the severity of diabetic retinopathy [43][44][45]. In most cases, however, serum CML levels strongly correlate with HbA 1c [46], suggesting that serum CML may not provide any additional risk information beyond that provided by monitoring mean levels of glycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…CML is routinely used as a proxy of a total load of AGEs in various pathological situations and increased CML levels have been repeatedly reported in patients with T2DM and related complications [5][6][7] . To date, there are only very limited clinical data about AGE levels in GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Gluco-oxidation of proteins forms complex and irreversible molecules, which accumulate in the retinal vasculature of patients with diabetes and streptozotocin-induced diabetic rats (Hammes et al, 1999;Stitt et al, 1997) and have been implicated in the development of diabetic retinopathy (Boehm et al, 2004Genuth et al, 2005. Chronic exposure of the endothelium to AGEs has been shown to increase retinal vascular permeability in vivo (Stitt et al, 2000) and ex vivo (Leto et al, 2001).…”
Section: Pathophysiological Mechanism Of Ages Formation In Diabetic Rmentioning
confidence: 99%